The effectiveness of cold compresses for reducing perinium wound pain - Lolli Nababan; Sari Widya Ningsih (Universitas Aisyiyah Yogyakarta, 2021)
The purpose of this study is to determine the relationship between the independent variable and the dependent variable. Observe before and after cold compress on the sample to be selected. Determines whether Ho will be accepted or rejected and Ha accepted, and vice versa. The number of samples was 30 postpartum mothers with grade I and II episiotomy wounds. The results of the univariate analysis showed that from 30 respondents, 0% of respondents who experienced very mild pain became 11 respondents (36.7%) after cold compresses, 15 respondents (50%) had mild pain to 13 (43.3%), pain moderate as many as 10 (33.3%) respondents to 6 (20%) respondents, severe pain as many as 5 respondents (16.7%) to 0 respondents. The result of p-value = 0,000, which means there is an effect of cold compresses on the healing of perineal wounds.